2020
DOI: 10.3390/su12239936
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Accounting—Cognitive and Conceptual Approach

Abstract: Nowadays, the speed of changes in practical activities and scientific research in the field of sustainable development has not yet allowed to clearly indicate the role of accounting in this area. Therefore, the main goal of the paper is to present sustainability accounting in the light of positive and normative accounting theory and to propose its conceptual framework as a normative solution. Positive theories allow the author to use inductive reasoning and thus indicates the state of accounting development (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 60 publications
0
6
0
1
Order By: Relevance
“…In order to prove that Islamic banking has a high importance for the social and economic development of the countries, which have inherited Islamic traditions, the authors have conducted a comparative analysis of Islam banking and IFRS by the following criteria: source of law, accountability, ownership of financial assets, social responsibility, accounting operations, consideration of the society interests, information disclosure, transparency and reliability. These factors emerge from the characteristic of a sustainable accounting system [1]. In case Islamic banking is in line with all of them, it's a significant and sustainable social institute.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to prove that Islamic banking has a high importance for the social and economic development of the countries, which have inherited Islamic traditions, the authors have conducted a comparative analysis of Islam banking and IFRS by the following criteria: source of law, accountability, ownership of financial assets, social responsibility, accounting operations, consideration of the society interests, information disclosure, transparency and reliability. These factors emerge from the characteristic of a sustainable accounting system [1]. In case Islamic banking is in line with all of them, it's a significant and sustainable social institute.…”
Section: Methodsmentioning
confidence: 99%
“…The accounting information system is a part of the economic information system of any organization and plays a leading role in planning, monitoring, organizing numerous activities, communication and motivation of personnel, being a resource for performing managerial functions [1]. It is the accounting information systems that provide stakeholders with the necessary information (in the form of accounting (financial), management (internal) reporting and reporting on sustainable development) which is the groundwork for making informed economic decisions of a financial and managerial nature, directed inward or outward, respectively [2].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that by belonging to a sustainability ranking, which is an innovation in accounting and reporting, enables a more accurate assessment of the level of sustainability performance, which, at the same time, promotes relationships with stakeholders. Zyznarska-Dworczak [45] proposes the use of a conceptual framework for sustainability accounting. Gonzalo and Garvey [46] comment that sustainability information should respect the principles related to sincerity and obtain a balance between the quantity and relevance of the information.…”
Section: Sustainability Accounting and Ifrsmentioning
confidence: 99%
“…Every topic belonging to each of these three sustainability dimensions can be converted into a distinct sustainability data item [66] by referring to sustainability accounting. This is an integrated financial system that defines the principles and procedures for measuring sustainability metrics [67,68]. The Global Reporting Initiative (GRI)-currently cooperating with the European Financial Reporting Advisory Group (EFRAG) to foster international convergence in sustainability reporting [69]-represents the most common methodology in practice to compute these evaluations.…”
Section: Sustainability Data Reporting and Digital Toolsmentioning
confidence: 99%